Iktiofauna di Sungai Batang Merangin dan Sungai Nilo Kabupaten Merangin, Jambi - Apriza Hongko Putra (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
This research aimed to inventory freshwater fish species in Batang Merangin River and Nilo river in Merangin Regency, Jambi. The research had been conducted from July- December 2018. It used descriptive survey method. Sampling of fish species was done purposively at 08.00 am-05.00am and 07.00pm-00am by using fishing rod, fishing net, fish spear, fishing fork. The result showed that totally 53 species of fish was catched classified to 16 families from Batang Merangin and Nilo river. In Batang Merangin was found 52 species, while in Nilo river was found 32 species. The families were Cyprinidae (22 species), Channidae (3 species), Mastacembelide (3 species), Botidae (2 species), Bagridae (7 species), Siluridae (2 species), Ospronemidae (2 species), Balitoridae (2 species), Pangasidae (2 species), Cynoglossidae (1 species), Clariidae ( 1 species), Akysidae (1 species), Notopteridae (1 species), Belonidae (1 species) , Cobitidae (1 species), dan tetraodontidae (1 species). Keywords: Ichtyofauna, Batang Merangin river, Nilo river.